Lindernia aculeata (Bonati) T. Yamaz. (Scrophulariaceae) newly recorded for Thailand - Chuakul, Wongsatit (Thai Forest Bulletin (Botany), 2014)
Lindernia aculeata is reported for the first time in Thailand, with a full description and illustrations.